Effective Use of Recreation Resources of South Uzbekistan : Penggunaan Sumber Daya Rekreasi yang Efektif di Uzbekistan Selatan - Allakulovich, Allanov Kilich; Kodirovich, Choriev Abdikayim (Indonesian Journal of Innovation Studies, 2023)
In this article, the geographical location of the Surkhandarya region of the Republic of Uzbekistan, its healing springs and their importance in the treatment of diseases, the beautiful and fresh air natural areas in the mountain and sub-mountainous regions, and the construction of health centers that meet world standards in these regions, as well as some issues of the further development of the recreational sector in the region problems, as well as the issues that should be resolved in their elimination are highlighted.